A note from Head Centre of Study / Prof. Madya Dr. Azila Azmi - Azmi, Azila (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Congratulations to the writers and contributors of the FPHP Bulletins - Hot & Tour Newsletter Series 1 and Series 2. The FPHP Bulletins - Hot & Tour Newsletter serves as a platform for academics to present their writings in Series 1 and to share updates on the faculty's annual activities in series 2.